Impaired Resolution of Inflammation in the Endoglin Heterozygous Mouse Model of Chronic Colitis - Madonna R. Peter; Mirjana Jerkic; Valentin Sotov; David N. Douda; Daniela S. Ardelean; Niousha Ghamami; Flavia Lakschevitz; Meraj A. Khan; Susan J. Robertson; Michael Glogauer; Dana J. Philpott; Nades Palaniyar; et al. (Mediators of Inflammation)
Endoglin is a coreceptor of the TGF-β superfamily predominantly expressed on the vascular endothelium and selective subsets of immune cells. We previously demonstrated that Endoglin heterozygous (Eng+/−) mice subjected to dextran sulfate sodium (DSS) developed persistent gut inflammation and pathological angiogenesis. We now report that colitic Eng+/− mice have low colonic levels of active TGF-β1, which was associated with reduced expression of thrombospondin-1, an angiostatic factor known to activate TGF-β1. We also demonstrate dysregulated expression of BMPER and follistatin, which are extracellular regulators of the TGF-β superfamily that modulate angiogenesis and inflammation. Heightened colonic levels of the neutrophil chemoattractant and proangiogenic factor, CXCL1, were also observed in DSS-treated Eng+/− mice. Interestingly, despite increased macrophage and neutrophil infiltration, a gut-specific reduction in expression of the key phagocytic respiratory burst enzymes, NADPH oxidase 2 (Nox-2) and myeloperoxidase, was seen in Eng+/− mice undergoing persistent inflammation. Taken together, these findings suggest that endoglin is required for TGF-β superfamily mediated resolution of inflammation and fully functional myeloid cells.